Early career researchers in ornithology: attitudes, career prospects and gender issues (Avocetta, 2019)
Early Career Researchers (ECRs) represent the next generation of ornithologists. In order to maximise the potential of ECRs to science, it is important to understand their perceptions of the opportunities and constraints that they face. We undertook a pilot study based on a questionnaire survey to gauge attitudes of ECRs in ornithology towards the current research environment, future career prospects, and gender bias. ECRs were defined as having less than five years’ post-doctoral experience. The ECRs surveyed included BSc and MSc students, PhD students and post-doctoral researchers. The goal of the majority of ECRs was a career in academia, but there was also interest in working for non-governmental organisations (NGOs). Career prospects were perceived as increasingly negative from BSc/MSc students through to postdocs, likely reflecting a career bottleneck at the post-doctoral level. The influence of Twitter, open access publishing, open access data and journal Impact Factors were generally perceived as positive, although many BSc/MSc students had apparently little awareness of these initiatives. Female, but not male, ECRs perceived their gender to have a negative influence on their job prospects, and also were less likely to agree that a research career was compatible with having a family/partner. Our findings could be used to help ECRs to fulfil their ambitions in terms of establishing a career in ornithology. We suggest that provision of better support, communication and training to ECRs, as well as continuing initiatives to address gender bias, will improve the research environment for the next generation of ornithologists. These goals could be achieved through targeted events at national and international conferences and through enhanced communication on social media platforms.
Keywords: Twitter; questionnaire survey; gender bias; career prospects